HAK ASASI MANUSIA PERSPEKTIF AGAMA KRISTEN - Jamiliya Susantin (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2018)
Human rights is a set of rights attached to the nature and existence of human beings as God's omnipresent beings and is a gift that must be respected, upheld and protected by the state law, government, and every other person for the honor and protection of human dignity and prestige. Human rights, especially Christians have been protected by the 1945 Constitution and have several rights that can guarantee the welfare of those rights: Freedom rights, democratic rights, and social rights that are also contained in the Constitution 1945